Thinking about research and creative endeavour - Olivier, Gerrit (Arts Research Africa (ARA), 2020)
Are the binary oppositions postulated between theoretical and practical knowledge, and between western and African philosophy—as in the call for this conference—valid or useful for artistic research? This paper asks where this conceptual division should best be located and poses the question of whether it is valid, sustainable, and helpful to distinguish between African and European “modes of knowledge.”
Arts Research Africa Conference Proceeding 2020
Keywords: Artistic research; Arts research; Decolonisation; Arts pedagogy